Conditional associations of sex steroid hormones with C-reactive protein levels in American children and adolescents: evidence from NHANES 2015-2016 - Zhu, Zhisheng; Lin, Xingong; Wang, Chaoyang; Zhu, Shize; Zhou, Xianying (Frontiers in Endocrinology, 2024)
The relationship between sex steroid hormones and high -sensitivity C-reactive protein(hs-CRP) levels in American children and adolescents is understudied. This research will examine this association.: The study conducted a data analysis from the National Health and Nutrition Examination Survey (NHANES) 2015 -2016, adjusting multiple linear regression models with R 4.2.2 and EmpowerStats. A total of 1,768 children and adolescents were surveyed.Data collection involved measurements of serum levels of testosterone, estradiol, sex hormone -binding globulin (SHBG) and hs -CRP.Results:With the increase in testosterone, a brief rise ( β=0.082, P=0.047) followed by an overall decline ( β=-0.028, P=0.023) in hs-CRP was observed in the Male Prepubertal population, while a continuous decline ( β=-0.002, P<0.05) was seen in the Male Pubertal group. A positive correlation ( β=0.047, P<0.05) was found between testosterone and hs -CRP in the Female Prepubertal population, whereas no significant association ( β=0.002, P>0.05) was detected in the Female Pubertal group. A significant inverse corre lation was observed between estradiol and hs-CRP solely in the Female Pubertal group ( β=-0.002, P<0.05), while no association was found in other populations. An inverse relationship between SHBG and hs-CRP was consistently noted across all groups: Male Prepubertal, Male Pubertal, Female Prepubertal, and Female Pubertal.The association between sex steroid hormones and high -sensitivity C-reactive protein (hs-CRP) levels among American children and adolescents is conditional and influenced by multiple factors.